Video as an Educational Medium for Preparation for Childbirth in Primigravida in the Archipelago - Vina Jayanti; Dewi Mey Lestanti Mukodri; Kartika Sri Dewi Batubara (Aloha International Journal of Health Advancement (AIJHA), 2022)
Pregnancy and childbirth for primigravida mothers are very special and are very much awaited. A pregnant woman must obtain much information about preparation for childbirth when checking her pregnancy at a health facility. However, due to limited access, pregnant women in the archipelago region do not get information about preparation for childbirth. One of the innovations so pregnant women in the islands can reach that information on childbirth preparation is providing information through video. This delivery preparation video can be accessed by primigravida mothers with their families at home so that they are expected to be physically and mentally ready to face the labor process. This study aimed to determine the effect of childbirth preparation videos on readiness for childbirth in primigravida pregnant women in the third trimester. This research was quasi-experimental with a nonequivalent control group design. The research was conducted at one of the Public Health in Tanjungpinang. The population was primigravida pregnant women in the third trimester, consisting of 60 respondents with the purposive sampling technique. The sample was divided into 2 groups; 30 respondents in the treatment group and 30 respondents in the control group. The results showed differences in the post-test readiness scores of the treatment and control groups with a p-value